India, Water and Sustainable Development - Bachhuber, Daniel (Consilience, 2009)
Author’s Note: India faces tremendous developmental challenges, both in water and other sectors, in the next couple of decades. My three-month journey in spring 2008 was, at its core, an exploration of the myriad of complexities to providing safe and sustainable water access. I hope the images will lend an insightful introduction to the challenges of the subcontinent and inspire a desire to learn more. Introduction: In February 2008, I took a break from academic studies for three months of real-life study: trying to understand India’s cultural, social and religious constraints to clean water access. The subcontinent has the second largest population in the world, and nearly a quarter of its peoples are lacking access to safe and reliable water. I set out to discover and document this issue. After landing in Delhi, I traveled to Kanpu, Allahabad and Varanasi, all sites along India’s most famous and-arguably-most toxic river because of heavy domestic and industrial pollution. From there, I went south to the Western Ghats and then northeast to the Kolwan Valley, where stories of complex political dynamics lived in every village. Traveling onward to Mumbai, it was a story of socio-economic inequalities. Finally I ended up in Rajasthan, where the biggest issue is also the most basic: there simply is not nearly enough water. Overall, the journey was an eye-opening exploration of India’s biggest challenge in the coming decade: clean and sustainable water access for all of its citizens. Works Cited: Gupta, Anurag, NGO employee. Interview by author. 4 April 2008. Joshi, Leena. Interview by author. 27 March 2008.